Effectiveness, acceptability and potential harms of peer support for self-harm in non-clinical settings: systematic review. Issue 1 (17th January 2022) - Abou Seif, Nada; John-Baptiste Bastien, Rayanne; Wang, Belinda; Davies, Jessica; Isaken, Mette; Ball, Ellie; Pitman, Alexandra; Rowe, Sarah
Abstract : Background: Many people who have self-harmed prefer informal sources of support or support from those with lived experience. However, little is known about whether peer support improves outcomes for people who have self-harmed or about the risks of peer support interventions in non-clinical settings. Aims: The aims of this review were to examine the effectiveness, acceptability and potential risks of peer support for self-harm, and how these risks might be mitigated. Method: We searched bibliographic databases and grey literature for papers published since 2000. We included peer support for self-harm that occurred in voluntary-sector organisations providing one-to-one or group support, or via moderated online peer support forums. Results: Eight of the ten papers included focused on peer support that was delivered through online media. No study compared peer support with other treatments or a control group, so limited conclusions could be made about its effectiveness. Peer support for self-harm was found to be acceptable and was viewed as having a range of benefits including a sense of community, empowerment, and access to information and support. The most commonly perceived risk associated with peer support was the potential for triggering self-harm. Conclusions: Our findings highlighted a range of benefits of being part of a group with very specific shared experiences. Mitigations for potential risks include organisations using professional facilitators for groups, trigger warnings for online forums, and providing regular supervision and training so that peers are prepared and feel confident to support vulnerable people while maintaining their own emotional health.